Using Google Street View photographs to assess long-term outdoor thermal perception and thermal comfort in the urban environment during heatwaves - Urban, Jan; Pikl, Miroslav; Zemek, František; Novotný, Jan (Frontiers in Environmental Science, 2022)
The outdoor thermal comfort of urban residents is negatively affected by heatwaves that are becoming more frequent and severe with the ongoing climate crisis. As such, the assessment of outdoor perception and comfort during heatwaves has become an important ingredient of successful urban adaptation strategies. However, systematic assessment of long-term thermal perception across a large number of places and large populations of people is difficult. In this study, we consider an approach to the assessment of long-term thermal perception that combines features of currently used approaches (i.e., use of rating scales of thermal perception, use of surveys, and the use of photographs representing places) and we provide some preliminary validation of this approach. Specifically, across three studies conducted in two Czech cities, we show that long-term thermal perceptions for a large sample of 1,869 urban places can be elicited in a large sample of city residents (total N = 1,877) using rating scales in off-site surveys complemented with visual representations of the target locations. In Studies 1 and 2, we partially validate this approach by showing that such long-term thermal perceptions can be traced back to average surface temperature, sky-view factor, and the presence of blue and green infrastructure, all factors that the literature relates to thermal perception. Moreover, we show evidence that observers can reliably glean these properties from the visual representation of places. In Study 3, we provide additional evidence of the predictive validity of such long-term thermal perceptions by showing that they predict place-related activities (waiting and walking) and the place preference of other people more than one year later. Thus, this approach to the measurement of long-term thermal perception related to heat waves can be a useful addition to currently used approaches.